DICTION ANALYSIS IN CHARLOTTE PUDDIFOOT’S POEM AFTER THE ABORTION - Meliana Siboro; Rahmadsyah Rangkuti; M Manugeren (Universitas Islam Sumatera Utara (UISU), 2022)
This research aims to analyze the use of diction in the poem After The Abortion by Charlotte Puddifoot. The poem deals with matters of abortion experienced by women. The process of aborting a pregnancy intentionally is a mechanism to make a fetus in the uterus unable to develop or stay. In a simple concept abortion is a killing. The research method is a descriptive qualitative method with close reading technique to collect data. Data were classified into four general types of diction: abstract, concrete, denotative and connotative. The finding shows the use of abstract, concrete, denotative and connotative are prevalent throughout the poem, with concrete diction being the majority. Each line of the poem is carefully structured with effective diction to send the author’s message to the reader. Abstract, concrete, denotative and connotative dictions are used to create imagery and vivid pictures of the procedures. The poem carries a heavy lesson of physical and long-term emotional damages caused by abortion.